Detection and quantification of airborne viral and bacterial pathogens associated with bovine respiratory disease complex - Alshammari, Askar (2022)
Airborne pathogens are considered to be sources of respiratory disease infection in calf barns. Different types and quantities of airborne pathogens are present in calf barns and are associated with bovine respiratory disease complex (BRD). In order to detect these airborne pathogens, Oxoid and MD8 air samplers were used inside of a barn for collecting air samples. However, air sampler devices, sampling volume, and sampling duration remain unclear for collecting airborne pathogens from calf barns. Therefore, this study aimed to detect and quantify airborne viral and bacterial pathogens associated with BRD complex. The pilot study aimed to determine the optimum conditions for the use of air samplers, as well as to isolate total airborne bacteria inside of the calf barn and determine colony-forming unit (CFU) counts using an Oxoid air sampler. Furthermore, the longitudinal study aimed to collect nucleic acid from total airborne bacteria and viruses using an MD8 sampler to allow the detection and quantification of RNA for parainfluenza 3 virus (PI3) and bovine respiratory syncytial virus (BRSV), and of DNA for bovine herpesvirus 1 (BoHV-1), and the total bacteria through the use of qPCR assays. The pilot study results showed that the optimal air volumes using an Oxoid air sampler on blood agar plates (BA) and eosin methylene blue plates (EMB) for collecting the total bacteria inside of the barn were 10 and 25 litres, respectively. These air volumes were relatively consistent with the low variance in microbial counts in replicate samples. Similarly, the volume for collecting air samples on gelatine filters using an MD8 sampler was 800 litres, which was chosen to shorten the sampling time so as not to disturb the calves. The results from the longitudinal study for microbial counts showed different microbial numbers inside of the barn, and the CFU of the gram-positive bacteria (18,219 ± 11,676 (SD) CFU/m3) was higher than that of the gram-negative bacteria (2,013 ± 1,111 (SD) CFU/m3). Both bacteria were not affected by barn factors such as temperature, humidity, and the number of calves. Additionally, we found that the younger calves below the age of six weeks were more susceptible to BRD than were those above the age of six weeks.